Effectiveness of digitalization towards retailing business - Siew, Edward Jun Fung; Lee, Jia Xin (2018)
This study was aimed to investigate effectiveness of digitalization in retail business in Klang Valley area. To specifically examine the indepth of digitalization in retail business, background and issues related to the research topic has been discussed. This study is designed to achieve the following objectives: (1) To investigate the relationship between perceived personalization and customer experience; (2) To investigate the relationship between perceived interactivity and customer experience; (3) To investigate the relationship between customer experience and customer satisfaction; (4) To investigate the relationship between perceived personalization and customer satisfaction; (5) To investigate the relationship between perceived interactivity and customer satisfaction; (6) To investigate the mediation effect of customer experience between perceived personalization and customer satisfaction; (7) To investigate the mediation effect of customer experience between perceived interactivity and customer satisfaction. This research may also be beneficial to certain parties such as retail business, government, future researchers and customer. Furthermore, reviews of literature by previous author and researcher are provided in order to further explain the association between the variables and the explanation of digitalization in retail business. In this research, data are collected from primary sources where questionnaires are distributed to 300 respondents in Klang Valley area using convenient sampling technique, in which the respondent who have experiences with online shopping. Statistical Package for the Social Sciences (SPSS) software version 21 is used to carry out the research to construct new findings in the relationship between perceived personalization, perceived interactivity, customer experience and customer satisfaction. The results and findings are then demonstrated in few different parts which included descriptive analysis for demographic profile, constructs for central tendencies measurement, measurement of scale and the inferential analysis. Last but not least, all the findings in the research are concluded in the last chapter. Implications of the study are also further described, as well as the limitations of the study. Not to mention, several recommendations for future research are provided in order to sums up the entire completed research.